VARK (Visual, Auditory, Read/Write and Kinesthetics) Model with Digital Scrapbook for Improving Al-Quran Reading Skills - Susandi, Ari; Zativalen, Oriza; Mulyono, Khubby; Laili, Viviana Nisful; Irmaningrum, Rizka Novi (Pedagogia : Jurnal Pendidikan, 2025)
This study uses a research design adapted from Plomp (1997), which is considered a general model that is easy to apply in the development of learning models. The stages in this research include: (1) Initial investigation or preliminary study; (2) Design; (3) Realisation/Construction; (4) Expert validation test, pilot test, evaluation, and revision; and (5) Implementation. The main purpose of this research is to develop a learning model for primary school students, especially grade V students. The developed learning model refers to VARK (Visual, Auditory, Read/Write, and Kinesthetic) based on Digital Scrapbook. This model aims to familiarise students in reading the Qur'an well and improve their skills. This approach incorporates a variety of learning styles to support a thorough mastery of Qur'ānic reading skills. Digital Scrapbook-based VARK is designed to suit students' needs and facilitate variations in their ways of learning. This research is expected to produce an innovative learning model that is effective and easy to implement in the context of Islamic values-based basic education. Highlights: Improved Reading Ability: Students taught using the PQRST-STAD method with short videos performed better than those using picture series. Method Effectiveness: Short videos enhance the effectiveness of integrated PQRST-STAD for reading narrative texts. Future Recommendations: Further development is needed in designing creative and detailed video/image content for learning. Keywords: Digital Scrapbook, Al-Quran, Reading Skills